Pre-hospital telestroke and expanded hyper-acute telestroke network solutions to reduce geographic inequities: a brief review from the South Pacific - Ranta, Anna; Audebert, Heinrich J.; Ioane-Cleverley, Luatupu (Frontiers in Stroke, 2024)
Hyper-acute stroke treatments are time sensitive, and decision-making is complex. Telemedicine has been highly effective in breaking down regional access barriers by providing front line rural hospital clinicians with remote telemedicine decision support by remote stroke experts. With the advent of mechanical thrombectomy, hyper-acute stroke care has grown even more complex from both a decision-making and logistical perspective. Mobile Stroke Units (MSU) have been deployed in a few urban settings globally but are unlikely to address all global access issues due to geographical and logistical factors. This paper reviews the feasibility and benefit of extending telestroke into the prehospital setting as an adjunct or alternative to MSUs. It will discuss how this service model can fit into existing stroke networks and potential deployment strategies. Finally, the paper also considers potential scalability of pre-and in-hospital telestroke support across regional and international boundaries to further reduce global hyper-acute access inequities.